Clinical application of next generation sequencing in lymphoma. Issue 4 (21st March 2021) - Scott, Anthony J.; Tokaz, Molly C.; Shango, Maryann; Devata, Sumana; Carty, Shannon A.; Kaminski, Mark S.; Chinnaiyan, Arul M.; Phillips, Tycel J.; Wilcox, Ryan A.
Abstract: Successful treatment of relapsed/refractory and rare subtypes of lymphomas remains a therapeutic challenge. Though the use of tumor profiling is increasing, little is described about how providers ultimately utilize this information in clinical decision-making. We reviewed 92 adult lymphoma patients who underwent an IRB-approved tumor sequencing protocol at the University of Michigan, MI-ONCOSEQ. Of this cohort, 60 had a targeted treatment suggested by their test results, and 11 patients ultimately underwent the MI-ONCOSEQ recommended therapy. One obtained complete response based on precision treatment recommendations. The two main barriers for targeted treatment utilization included inopportune timing (the patient either was sequenced too early or too late in their disease course) and clinical trial availability. While this study demonstrates the success of sequencing lymphomas for the identification of novel therapies, it also underlines the clinical challenges, namely the optimal timing and availability of trials, inherent in the successful application of this technology.